If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 3) = -36 + -4x Reorder the terms: 2(3 + 5x) = -36 + -4x (3 * 2 + 5x * 2) = -36 + -4x (6 + 10x) = -36 + -4x Solving 6 + 10x = -36 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 10x + 4x = -36 + -4x + 4x Combine like terms: 10x + 4x = 14x 6 + 14x = -36 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 14x = -36 + 0 6 + 14x = -36 Add '-6' to each side of the equation. 6 + -6 + 14x = -36 + -6 Combine like terms: 6 + -6 = 0 0 + 14x = -36 + -6 14x = -36 + -6 Combine like terms: -36 + -6 = -42 14x = -42 Divide each side by '14'. x = -3 Simplifying x = -3
| 9.12*9.12= | | 10y=2y+72 | | 9.11*9.11= | | 9.15*9.15= | | -31+3a=4(a-7) | | x+3(2x+5)=6 | | -8(1+3x)-6x=172 | | n-8=19-11 | | 9.21*9.21= | | n^2-12n+13=-7 | | 3(r-5)+2(r-4)=-2(r-1)+8(r+2) | | 8(7r+5)=320 | | 6x-5=109 | | 8(7r+5)=330 | | e^4x=e^2x+6 | | 2/3=2-2 | | 2a+14-13=-7 | | a^2+8a+6=-9 | | b-33=145 | | 4+2(2)+3x=11 | | 6(1-5v)=-234 | | 6-2n=-8+3(-4n-2) | | 1-3y/5-4=2y/3 | | 4(3x-5)-12(x-5)=70 | | 1+3x=4+4x | | (2x-7)y=15 | | x=x-u | | -10-9k=-91 | | -8x-3x-11=-8x+7 | | 3x-10(x+2)=sqrt(13)-7x | | -8x-3x-11=-8+7 | | 99=5n+9 |